Europe - Smith, B. (engraver):::Creator::::::::::::; Arrowsmith, Aaron, 1750-1823 (cartographer):::Contributor:::::::::::: (London; Longman Hurst Rees and Orne; United Kingdom)
Engrave map of Europe from the early 19th century.